Effect of exercise training in rats exposed to chronic hypoxia: Application for Monge's disease. Issue 7 (27th April 2021) - Macarlupu, José‐Luis; Marchant, Dominique; Jeton, Florine; Villafuerte, Francisco; Richalet, Jean‐Paul; Voituron, Nicolas
Abstract: Physical exercise may improve hematological conditions in high altitude dwellers suffering from Chronic Mountain Sickness (CMS), in reducing hemoglobin concentration. Therefore, the present study aimed to characterize the effects of 1‐month exercise training session in a model of rats exposed to chronic hypoxia. Four groups of male rats were studied: normoxic sedentary (NS, n = 8), normoxic training (NT, n = 8), hypoxic sedentary (HS, n = 8), and hypoxic training group (HT, n = 8). Hypoxic groups were exposed to hypobaric hypoxia for one month (PB =433 Torr). Training intensity was progressively increased from a running speed of 10.4 to 17.8 m/min. Chronic hypoxia led to an increase in hematocrit (HCT) associated with a decrease in plasma volume despite an increase in water intake. Training led to a reduction in HCT ( p < 0.01), with a non‐significant increase in plasma volume and weight gain. Hypoxia and training had inhibitory effects on haptoglobin (NS group: 379 ± 92; HT: 239 ± 34 µg/ml, p < 0.01). Chronic hypoxia and exercise training increased SpO2 measured after acute hypoxic exposure. Training blunted the decrease in V ˙ O2 peak, time of exhaustion, and maximum speed associated with chronic exposure to hypoxia. Chronic hypoxia led to a right ventricular hypertrophy, which was not corrected by 1‐month exercise training. Altogether, by decreasing hematocrit, reducing body weight, and limiting performance decrease, training in hypoxia may have a beneficial effect on excessive erythropoiesis in chronic hypoxia. Therefore, regular exercise training might be beneficial to avoid worsening of CMS symptoms in high altitude dwellers and to improve their quality of life. Abstract : Exercise training limited chronic hypoxia‐induced decline in physical capacity. Exercise training decreased hematocrit through mechanical hemolysis. Exercise training in hypoxia have a beneficial effect on excessive erythropoiesis